PENGARUH FAKTOR BUDAYA ORGANISASI, MOTIVASI, PEMBERDAYAAN & LINGKUNGAN TERHADAP KINERJA ORGANISASI (STUDI KASUS PERGURUAN TINGGI SWASTA DI BANDAR LAMPUNG) - rika, winda (Jurnal Manajemen dan Keuangan, 2012)
The leader has important role in increasing organization performance and increasing or decreasing lecturersâ work satisfaction. Besides the organization performance factors, there are many factors influencing a lecturer work satisfaction level or achievement namely organization culture, motivation (work spirit), empowerment, and conducive environment. The increasing of culture, motivation, work empowerment and environment are expected to increase organization performance and at last to increase lecturersâ satisfaction. The aims of the research are 1) to know influence partially toward organization culture, motivation, work improvement and environment toward organization performance, 2) to know the influence simultaneously of organization culture, motivation, empowerment and environment toward organization performance in private college in Bandar Lampung. The result of the research indicates that organization culture, motivation, empowerment and environment have positive and significant influence toward organization performance level. The influence level simultaneously in organization performance is 0.66 (66%). Based on the result, it can be concluded that hypothesis indicating organization culture, motivation, improvement and environment variables, which has significant contribution toward organization performance, can be accepted. Moreover, organization culture, motivation, work empowerment and environment have influence toward performance organization individually. The influence levels are: organization structure contributing directly toward organization performance is 0.19, motivation contributing directly toward organization performance is 6.25%, empowerment contributing toward organization performance is 4.41% and environment contributing toward organization performance is 25%.Keywords: Organization Culture, Motivation, Empowerment, Environment, Organization performance, and Work Satisfaction.